Structure–Activity Relationships for Hypervalent Iodine Electrocatalysis - Frey, Brandon L.; Thai, Phong; Patel, Lauv; Powers, David C. (Synthesis, 2023)
The design and optimization of novel electrocatalysts requires robust structure–activity data to correlate catalyst structure with electrochemical behavior. Aryl iodides have been gaining attention as metal-free electrocatalysts but experimental data are available for only a limited set of structures. Herein we report electrochemical data for a family of 70 aryl iodides. Half-peak potentials are utilized as proxies for reduction potentials and reveal that, despite differences in electrochemical reversibility, the potential for one-electron oxidation of 4-substituted aryl iodides to the corresponding iodanyl radicals is well-correlated with standard Hammett parameters. Additional data are presented for 3- and 2-substituted aryl iodides, including structures with potentially chelating 2-substituents that are commonly encountered in hypervalent iodine reagents. Finally, potential decomposition processes relevant to the (in)stability of iodanyl radicals are presented. We anticipate that the collected data will advance the design and application of aryl iodide electrocatalysis.
Keywords: hypervalent iodine; electrochemistry; linear free-energy relationships; sustainable catalysis; oxidation